Emotional discrimination during viewing unpleasant pictures: timing in human anterior ventrolateral prefrontal cortex and amygdala - Kohno, Satoru; Noriuchi, Madoka; Iguchi, Yoshinobu; Kikuchi, Yoshiaki; Hoshi, Yoko (Frontiers in Human Neuroscience, 2015)
The ventrolateral prefrontal cortex (VLPFC) and amygdala have critical roles in the generation and regulation of unpleasant emotions, and in this study the dynamic neural basis of unpleasant emotion processing was elucidated by using paired-samples permutation t tests to identify the timing of emotional discrimination in various brain regions. We recorded the temporal dynamics of blood-oxygen-level-dependent signals in those brain regions during the viewing of unpleasant pictures by using functional magnetic resonance imaging with high temporal resolution, and we compared the time course of the signal within the volume of interest across emotional conditions. Results show that emotional discrimination in the right amygdala precedes that in the left amygdala and that emotional discrimination in both those regions precedes that in the right anterior VLPFC. They support the hypotheses that the right amygdala is part of a rapid emotional stimulus detection system and the left amygdala is specialized for sustained stimulus evaluation and that the right anterior VLPFC is implicated in the integration of viscerosensory information with affective signals between the bilateral anterior VLPFCs and the bilateral amygdalae.